Acceptability of government measures against COVID-19 pandemic in Senegal: A mixed methods study - Valéry Ridde; Babacar Kane; Ibrahima Gaye; Mouhamadou Faly Ba; Amadou Diallo; Emmanuel Bonnet; Zoumana Traoré; Adama Faye (Public Library of Science (PLoS), 2022)
While the first case of COVID-19 was declared on March 2 2020 in Senegal, the government banned the attendance of places of worship on 14 March, as a first measure. On March 23, it introduced a curfew, a ban on movement between regions, and the closure of markets. The objective of this study is to measure and understand the acceptability of these four governmental measures as well as the level of public trust in the state to fight the pandemic. We carried out a mixed-method research. The acceptability variables were defined using the theoretical framework of acceptability (TFA). At the quantitative level, we carried out a telephone survey (June/July 2020) at the national level (n = 813) with a sampling strategy by marginal quotas. We conducted a qualitative survey (August/September 2020) with a nested sample (n = 30). The results show a relatively high acceptability of the measures but a heterogeneity of responses. People considered curfews to be much more important (85.7% [83.2%; 88.0%]) than the closure of places of worship (55.4%; [51.9%; 58.7%]), which is least in line with the values and positive affective attitude. Several positive unintended effects of the curfew were stated (security and social/family cohesion). People over the age of 60 have more confidence in the government to fight the pandemic than people under the age of 25, although not significant (7.72 ± 3.12 vs. 7.07 ± 3.11, p = 0.1); and they are more in favour of the closure of places of worship. The more regions are affected by the pandemic, the less confidence respondents report in the government and the less they perceive the measures as effective. The results confirm the importance of government communication and trust in the state to strengthen the acceptability of pandemic measures. Important differences in acceptability show the need to adapt measures and their explanations, instead of unqualified universal action.